Factors Affecting Budgeting: Leadership Style, System and Resource Refinement - Cris Kuntadi; Djamal Firmansyah (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to map the influence of leadership styles, systems, and the improvement of resources on budgeting. The independent variables are leadership style, systems, and increased resources while the dependent variable is budgeting in the study of the State Financial Management Library. The purpose of this study as a literature review is to build hypotheses about the influence of variables to be used in further research. This research method is a qualitative method and literature review (Library Research). Examine theories and relationships or influences between variables from books and journals both online sourced from Mendeley, Scholar Google, and other online media. Based on the results of this literature review article, it is known that leadership style influences budgeting, system improvement affects budgeting, and resources affect budgeting.